If pq + 1 = q

^{2}and t = (frac{1}{p}) – (frac{1}{pq}) express t in terms of q-
**A.**

(frac{1}{p – q}) -
**B.**

(frac{1}{q – 1}) -
**C.**

(frac{1}{q + 1}) -
**D.**

1 + 0 -
**E.**

(frac{1}{1 – q})

##### Correct Answer: Option C

##### Explanation

Pq + 1 = q^{2}……(i)

t = (frac{1}{p}) – (frac{1}{pq})………(ii)

p = (frac{q^2 – 1}{q})

Sub for p in equation (ii)

t = (frac{1}{q^2 – frac{1}{q}}) – (frac{1}{frac{q^2 – 1}{q} times q})

t = (frac{q}{q^2 – 1}) – (frac{1}{q^2 – 1})

t = (frac{q – 1}{q^2 – 1})

= (frac{q – 1}{(q + 1)(q – 1)})

= (frac{1}{q + 1})